Primary carcinoma of the fallopian tube in a patient after strumectomy due to thyroid carcinoma: case study - Sobczuk, Anna; Wrona, Marcin; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2006)
In the study a case of primary carcinoma of the fallopian tube in a patient after strumectomy due to thyroid carcinoma is presented. This patient was hospitalized in our clinic three times from March to June 2006. In this time the diagnosis of dysplasia colli uteri, polypus endometrialis, carcinoma endometrioides, carcinoma oviductuum bilateralis was established. The analysis of the case confirms lack of characteristic symptoms of this carcinoma, difficulties with diagnosis, late recognition and bad prognosis.